Nation-building through history education: Mutual goals in shaping student character - Abang Mohd. Razif Abang Muis; Siti Aidah Lukin @ Lokin; Shapiza Sharif; Zanariah Hamid; Nirwana Mohd Rashid (ResearchGate, 2024)
Mutual goals are essential within the framework of nation-building, which depends on fostering moral virtues through the instruction of history. This study aims to examine the impact of history education on nation-building by investigating the interconnected elements of knowledge, moral sensitivity, and moral behaviour. By focusing on the Malaysian context, this research explores how history education contributes to national cohesion and economic success, fostering a shared national identity and instilling values such as patriotism, loyalty, and moral integrity among students. Unlike other studies that have explored the broader role of education in nation-building, this research delves into the specific influence of history education on shaping student character and promoting civic engagement. Through a comprehensive literature review and thematic analysis, the study develops a theoretical framework highlighting the significance of history education in transmitting historical knowledge, fostering ethical growth, and encouraging active participation in civic affairs. The findings underscore the importance of prioritizing history education in national curricula to cultivate informed, morally upright, and engaged citizens, ultimately contributing to a harmonious and progressive society.